Effect of biodegradable PLA on hydroxyapatite coating to improve adhesion properties on Cr-Co-Mo alloy - Mas Ayu, H. (2020)
Biomedical implants of Cobalt-Chromium-Molybdenum (Co-Cr-Mo) alloys have been reported difficult to bond directly on bone when inserted in human body. In order to improve this situation several attempts have been made including coating the implants with a bioactive layer such as hydroxyapatite (HA). However, major concerns arise when massive micro crack surface, delamination and low adhesion strength of HA coatings occurred which later caused the harmful releases of metal ions. The objectives of this research is to improve the adhesion strength of HA and produce crack free surface coating by adding biodegradable polylactic acid (PLA) into HA slurry as well as to enhance biocompatibility of Co-Cr-Mo alloy for long term used. In this research, the optimum HA slurry was determined by mixing different weight of PLA (1, 2 and 3 gram) before deposited on Co-Cr-Mo substrates using dip coating machine. Constant parameters for dip coating process were applied to all samples condition. Micro hardness test was done to measure the adhesion strength of the PLA/HA coating as well as to evaluate the effects of adding PLA at different weight. The corrosion resistance performance of the coated and uncoated Co-Cr-Mo substrates were investigated using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The results also proved that the mixture of 2g PLA with 1g HA into 20ml chloroform able to eliminate micro cracks with acceptable coating thickness (~10μm). It is concluded that by adding a suitable amount of PLA into HA slurry able to gain positive effect in terms of increment of the adhesion strength of HA coating as well as bioactivity performance.